Water sector governance: a return ticket to anarchy - Wegerich, Kai; Warner, Jeroen; Tortajada, Cecilia (International Journal of Water Governance, 2014)
A political-science perspective of anarchy holds that anarchy is the absence of a ruler. In the water sector, especially in terms of irrigated agriculture, emerging deficiencies of public irrigation systems as well as the budget crisis of governments to sustain irrigated agriculture, resulted into increased water user participation. Understanding the apparently increasing smidgeon of anarchy in the water sector includes the appreciation of the complexity of water governance developments such as the introduction of Participatory Irrigation Management (PIM), Irrigation Management Transfer (IMT), basin councils, Integrated Water Resource Management (IWRM) and Multi-Stakeholder Platforms (MSP), as well as the limited role of non-governmental organisations (NGOs) and grassroots organisations (GROs), for decades considered the ‘magic bullet’ in taking over and providing state services to the public. We conclude that governance is anarchy by other means.